The Vulcan Petawatt interaction facility - Danson, C; Brummitt, P; Collier, J; Clark, R; Dominey, M; Edwards, C; Edwards, R; Frackiewicz, A; Govans, J; Hancock, S; Hatton, P; Hawkes, S; et al. (2004)
The Vulcan Nd:glass laser at the Central Laser Facility (CLF) has recently been upgraded to the Petawatt level (10 15 Watts). The facility is now operational to the UK and international user community. During the first user experiments, the power and focussed intensity were increased gradually up to the Petawatt regime. Considerable experience has been gained operating the Vulcan facility in this mode. The Petawatt facility is designed to deliver irradiance on target of 10 21 W.cm -2 for a wide-ranging experimental programme in fundamental physics and advanced applications. This includes the interaction of super-high intensity light with matter, fast ignition fusion research, photon induced nuclear reactions, electron and ion acceleration by light waves and the exploration of the exotic world of plasma physics dominated by relativity.